Dynamics of trapped magnetic flux in superconducting FeTe₀.₆₅Se₀.₃₅ - Bondarenko, S.I.; Bludov, A.N.; Koverya, V.P.; Link, S.I.; Sivakov, A.G.; Timofeev, V.P.; Gawryluk, D.J.; Puźniak, R.; Wiśniewski, A. (Физика низких температур, 2017)
The magnetic moment in the superconducting and normal state of a crystalline FeTe₀.₆₅Se₀.₃₅ superconductor, grown by the Bridgman's method with relatively high growth rate, was measured. The temperature and magnetic field dependences of magnetization and its relaxation time were determined. Studied crystal, being non-uniform due to high growth rate of 5 mm/h, exhibits smaller width of superconducting transition in comparison with an ideal crystal grown with velocity of 1 mm/h, and the difference in magnetic properties of crystals grown with various growth rate, related to their microstructure, is discussed.